Collaborative electronic documentation in nurse-patient relationship : a systematic review - Iwuchukwu, Gift (My University, 2024)
Background: Evidence on collaborative electronic documentation practices is fragmented, particularly in clinical nursing settings. Legislative and documentation regulatory requirements necessitate patient involvement and availability of patient access to electronic health records. Patient access to EHR information has been cited to improve patient outcomes towards person-centered care, patient engagement, and enhanced collaborative relationship with care providers. Implementation protocols and approaches are needed to engineer adoption of patient collaboration in electronic documentation. Purpose: Collating and synthesizing collaborative electronic documentation practices in clinical settings; providing empirical evidence on facilitators, barriers, and outcomes of implemented and adoptable practices from service users perspective. Methods: Mixed-methods systematic review design. Database specific strategies and search terms were used to conduct 8 databases search in November 2022, including MEDLINE, Web of Science, Scopus, APA PsycINFO, ProQuest, CIANHL, COCHRANE and Google Scholar. The methodological quality of included studies was critically appraised using Mixed-Methods Appraisal Tool. A convergent approach was employed to transform and integrate quantitative and qualitative findings. Findings are presented in a narrative synthesis. Joanna Briggs Institute Reviewer’s Manual (JBI) and Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guided the review protocol and reporting of findings. Results: 16 studies were included in the review, comprising qualitative (n = 9), quantitative (n = 2) and mixed-methods (n = 5) study designs. Numerous strategies supporting collaborative electronic documentation were identified. Facilitators supporting CED practices included the perception of individual user, organization, and systems. The role of organizational participation through instilled guidelines and functional technological connectivity was emphasized. Positive and negative outcomes were patients’, nursing process and work process related. Conclusion: CED is a rapidly evolving subject but information concerning adoptable practices is still fragmented. The review highlights the need for more empirical research on the subject area to create awareness on the benefits to patients and simultaneously support adoption and implementation. The necessity for organization and end-user involvement in developing feasible practices, and educational training for both patients and clinicians is emphasized. Overall, the use of health technologies and integrated systems is highlighted to have great significance for patient care through collaborative electronic documentation practices.
Keywords: “collaborative electronic documentation”, “mixed-methods systematic review”, “nurse-patient relationship”, “electronic nursing documentation”, implementation strategies